A mouse model of ATRX deficiency with cognitive deficits and autistic traits - Katherine M. Quesnel; Nicole Martin-Kenny; Nathalie G. Bérubé (Journal of Neurodevelopmental Disorders, 2023)
Abstract Background ATRX is an ATP-dependent chromatin remodeling protein with essential roles in safeguarding genome integrity and modulating gene expression. Deficiencies in this protein cause ATR-X syndrome, a condition characterized by intellectual disability and an array of developmental abnormalities, including features of autism. Previous studies demonstrated that deleting ATRX in mouse forebrain excitatory neurons postnatally resulted in male-specific memory deficits, but no apparent autistic-like behaviours. Methods We generated mice with an earlier embryonic deletion of ATRX in forebrain excitatory neurons and characterized their behaviour using a series of memory and autistic-related paradigms. Results We found that mutant mice displayed a broader spectrum of impairments, including fear memory, decreased anxiety-like behaviour, hyperactivity, as well as self-injurious and repetitive grooming. Sex-specific alterations were also observed, including male-specific aggression, sensory gating impairments, and decreased social memory. Conclusions Collectively, the findings indicate that early developmental abnormalities arising from ATRX deficiency in forebrain excitatory neurons contribute to the presentation of fear memory deficits as well as autistic-like behaviours.